Advanced Nanoporous Anodic Alumina-Based Optical Sensors for Biomedical Applications - Feng, Silu; Ji, Weiwei (Frontiers in Nanotechnology, 2021)
Close-packed hexagonal array nanopores are widely used both in research and industry. A self-ordered nanoporous structure makes anodic aluminum oxide (AAO) one of the most popular nanomaterials. This paper describes the main formation mechanisms for AAO, the AAO fabrication process, and optical sensor applications. The paper is focused on four types of AAO-based optical biosensor technology: surface-Enhanced Raman Scattering (SERS), surface Plasmon Resonance (SPR), reflectometric Interference Spectroscopy (RIfS), and photoluminescence Spectroscopy (PL). AAO-based optical biosensors feature very good selectivity, specificity, and reusability.